PERTIMBANGAN ETIKA DALAM DISTRIBUSI ORGAN TRANSPLANTASI: TINJAUAN LITERATUR TERHADAP PRINSIP KEADILAN DAN PRIORITAS MEDIS - Alya Syab Baiturrahmi; Mutiara Anissa; Dessy Abdullah; Anita Darmayanti (Yayasan Nusantara Hasana Berdikari, 2025)
Organ transplantation is a vital medical solution that faces complex ethical dilemmas in the distribution of limited organs. This study aims to explore and analyze ethical considerations in the distribution of transplanted organs, focusing on the principles of justice and medical priority through a systematic literature review. The search methodology was conducted in the PubMed, ScienceDirect, and Google Scholar databases using the keywords